Elevated miR-182-5p Associates with Renal Cancer Cell Mitotic Arrest through Diminished MALAT-1 Expression - Kulkarni, Priyanka (Mol Cancer Res, 2018)
The molecular heterogeneity of clear cell renal carcinoma (ccRCC) makes prediction of disease progression and therapeutic response difficult. Thus, this report investigates the functional significance, mechanisms of action, and clinical utility of miR-182-5p and metastasis associated lung adenocarcinoma transcript 1 (MALAT1/NEAT2), a long non-coding RNA (lncRNA), in the regulation of kidney cancer using human kidney cancer tissues as well as in vitro and in vivo model systems. Profiling of miR-182-5p and MALAT-1 in human renal cancer cells and clinical specimens was done by quantitative real-time PCR (qPCR). The biological significance was determined by series of in vitro and in vivo experiments. The interaction between miR-182-5p and MALAT-1 was investigated using luciferase reporter assays. In addition, the effects of miR-182-5p overexpression and MALAT-1 downregulation on cell cycle progression were assessed in ccRCC cells. The data indicates that miR-182-5p is downregulated in ccRCC; the mechanism being CpG hypermethylation as observed from 5-Aza CdR treatment that decreased promoter methylation and expression of key methylation regulatory genes like DNMT1, DNMT3a and DNMT3b. Overexpression of miR-182-5p inhibited cell proliferation, colony formation, apoptosis and led to G2/M-phase cell cycle arrest by directly targeting MALAT-1. Downregulation of MALAT-1 led to upregulation of p53, downregulation of CDC20, AURKA, drivers of the cell cycle mitotic phase. Transient knockdown of MALAT-1 mimicked the effects of miR-182-5p overexpression. Finally, overexpression of miR-182-5p decreased tumor growth in mice, compared to controls; thus, demonstrating its anti-tumor effect in vivo.